Disrupting interferon-alpha and NF-kappaB crosstalk suppresses IFITM1 expression attenuating triple-negative breast cancer progression. (28th August 2021) - Provance, Olivia K.; Geanes, Eric S.; Lui, Asona J.; Roy, Anuradha; Holloran, Sean M.; Gunewardena, Sumedha; Hagan, Christy R.; Weir, Scott; Lewis-Wambi, Joan
Abstract: Overexpression of interferon induced transmembrane protein-1 (IFITM1) enhances tumor progression in multiple cancers, but its role in triple-negative breast cancer (TNBC) is unknown. Here, we explore the functional significance and regulation of IFITM1 in TNBC and strategies to target its expression. Immunohistochemistry staining of a tissue microarray demonstrates that IFITM1 is overexpressed in TNBC samples which is confirmed by TCGA analysis. Targeting IFITM1 by siRNA or CRISPR/Cas9 in TNBC cell lines significantly inhibits proliferation, colony formation, and wound healing in vitro . Orthotopic mammary fat pad and mammary intraductal studies reveal that loss of IFITM1 reduces TNBC tumor growth and invasion in vivo . RNA-seq analysis of IFITM1/KO cells reveals significant downregulation of several genes involved in proliferation, migration, and invasion and functional studies identified NF-κB as an important downstream target of IFITM1. Notably, siRNA knockdown of p65 reduces IFITM1 expression and a drug-repurposing screen of FDA approved compounds identified parthenolide, an NFκB inhibitor, as a cytotoxic agent for TNBC and an inhibitor of IFITM1 in vitro and in vivo . Overall, our findings suggest that targeting IFITM1 by suppressing interferon-alpha/NFκB signaling represents a novel therapeutic strategy for TNBC treatment. Highlights: Interferon induced transmembrane protein 1 (IFITM1) is overexpressed in a subset of TNBC. Loss of IFITM1 suppresses TNBC growth and invasion  in vitro and  in vivo which is associated with changes in NFkB signaling. IFITM1 expression is regulated by crosstalk between IFNa and NFkB signaling. Parthenolide inhibits NFkB and IFNa crosstalk to mitigate IFITM1 expression and subsequent TNBC progression.